THE INFLUENCE OF STUDENT ATTITUDES ON LEARNING ACHIEVEMENT - Iqbal, Muhammad; Farida, Linda Zaenati Nur; Win, Khin Than (LPPM Universitas Jambi, 2023)
This research is the first to examine the influence of attitude on learning outcomes among class X students of Senior high school 2 Jambi City. Attitude is one of the main indicators of current learning and learning outcomes are a benchmark for assessing student attitudes. The research aims to explore the relationship between student attitudes and their academic performance in various subjects. This research uses a quantitative research method by means of a survey with a purposive sampling technique. The analysis technique used is normality and linearity assumption testing and hypothesis testing using person correlation. The research subjects this time were 60 class X students of Senior high school 2 Jambi City. The results of this research show that the significance value is 0.042 which is smaller than 0.05, which shows that there is a sufficient relationship between student attitudes and student learning outcomes. The novelty of this research is that it introduces a new measure of student attitude based on a multidimensional scale that covers cognitive, affective, and behavioral aspects. The research also provides empirical evidence of the positive impact of student attitude on learning outcomes across different subjects, such as mathematics, science, and language. The research contributes to the literature on educational psychology and pedagogy by highlighting the role of student attitude in enhancing academic achievement and motivation.